2008
DOI: 10.1242/jcs.028647
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and activation of the Rac1 and Cdc42 GEF Asef in A431 cells stimulated by EGF

Abstract: Rac1 has a crucial role in epidermal growth factor (EGF)-induced membrane ruffling, lamellipodial protrusion, and cell migration. Several guanine nucleotide exchange factors (GEFs) including Sos1, Sos2, Tiam1 and Vav2 have been shown to transduce the growth signal from the EGF receptor to Rac1. To clarify the role of each GEF, we time-lapse imaged the EGF-induced activity change of Rac1 in A431 cells transfected with siRNA targeting each Rac1 GEF. Because knockdown of these GEFs suppressed EGF-induced Rac1 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 28 publications
8
48
0
Order By: Relevance
“…Our findings that Asef is required for bFGF-and VEGF-mediated angiogenesis raise the possibility that Asef and APC function downstream of growth factors acting through receptor tyrosine kinases. In line with this notion, we have recently found that Asef functions downstream of EGF and hepatocyte growth factor in epithelial cells (19,28). In this study, we showed that bFGF and VEGF induce the accumulation and colocalization of Asef and APC in membrane ruffles and lamellipodia and increase the amounts of the Asef-APC complex.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings that Asef is required for bFGF-and VEGF-mediated angiogenesis raise the possibility that Asef and APC function downstream of growth factors acting through receptor tyrosine kinases. In line with this notion, we have recently found that Asef functions downstream of EGF and hepatocyte growth factor in epithelial cells (19,28). In this study, we showed that bFGF and VEGF induce the accumulation and colocalization of Asef and APC in membrane ruffles and lamellipodia and increase the amounts of the Asef-APC complex.…”
Section: Discussionsupporting
confidence: 76%
“…48 Seemingly, the p120ctn/Cdc42/Rac1 pathway could be activated by constitutively active EGFR mutant in the absence of smoke exposure, eventually causing lung adenocarcinoma in patients who have never smoked. In addition to EGFR, 42,43 Rac1 and its downstream effects on cell motility could be activated by platelet-derived growth factor receptor 49 and insulin receptor, 50 as previously reported. Thus, the EGFR/p120ctn-dependent and EGFR/ p120ctn-independent pathways may be operative in smokers, former smokers, and nonsmokers.…”
Section: Rac1 Modulates Smoke-induced Migrationsupporting
confidence: 61%
“…43 These data highlight the potential significance of Rac1 in advanced disease as tumor-suppressing p120ctn is lost from cells. Activation of Rac1 via an EGFR/p120ctn-independent pathway is feasible because its activation is complex with multiple signaling inputs that include EGFR-independent receptor tyrosine kinases, integrins, and cadherins.…”
Section: Rac1 Modulates Smoke-induced Migrationmentioning
confidence: 89%
See 1 more Smart Citation
“…At the center of this new interface, Asef-Tyr175 hydrogen bonds to Asef-Asp209, Asef-Glu212, and also makes van der Waals contacts with Asef-Trp231 and Asef-Trp242 from the SH3 domain. Interestingly, AsefTyr175 has been reported to be a phosphorylation site by Src family tyrosine kinases, and could be involved in the regulation of the activity of Asef [31]. In addition to Asef-Tyr175, Asef-His173, Asef-His174, and Asef- His177 from the ABR region are also involved in this new interface with the SH3 domain ( Figure 6B).…”
Section: Wwwcell-researchcom | Cell Research Zhenyi Zhang Et Al 381mentioning
confidence: 99%